The Respons Growth and Yield Of Peanuts(Arachis hypogeae L.) On Dosage Bokashi Mixed Corn Sraw and Cow Manure - Sri Mulatsih; Farida Aryani; Gillang Agung Pratama (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This research aims to determine the effect of bokashi dose of mixture of corn straw and cow manure on growth and yield of peanuts and to determine the dose of bokashi mixture of cron straw and cow manure that could substitute for the use of inorganic fertilizers. The research was carried out from December 2021 to Marc 2022, located Pungguk Lalang Village, Curup Selatan sub district, Rejang lebong. This study used a non factorRandomized Block Design (RBD) consisting of 6 (six) treatments and 4 (four) replications, so that there were 24 (twentyfour) experimental units. The results showed that the dose of bokashi mixtureof corn straw and cow manure gave the best result s on the Growth and Yield of Peanuts at a dose level 10 tons/ha. The dose of bokashi mixture of corn straw and cow manure 10 tons.ha has provided optimal growth and yield of Peanuts and is equivalent to a dose of 300 kg/ha NPK fertilizer.